A "Book" of Psalms in 4QMidrEschata.b?. Issue 2 (3rd July 2019) - Willgren Davage, David
ABSTRACT: It is often argued that the Masoretic "Book" of Psalms is a carefully redacted collection whose final shape carries substantial interpretive significance. The way psalms are placed in sequence is deemed important, but the actual shapes of the earliest Dead Sea psalms scrolls are not often taken into account. The current article revisits these issues by situating them in their proper interpretive context—the late Second Temple period—and by looking at how a sequence of psalms commented upon in a pesher designated by Annette Steudel as 4QMidrEschat a.b is understood. The conclusion is that although sequences of psalms seem to have had significance in the selection of psalms, they did not affect the interpretation of the individual psalms.